SUPERCRITICAL CO2 - SURFACTANT WATER - DRUG - DRUG : ELECTRONIC INTERACTIONS . - Jara M., E. (2013)
The ( N , N -dimethyl -4 -nitroaniline ) indicator was used to characterize the electronic interactions with UV -Vis spectroscopy because of the solvatochromic property . As the polarizability / dipolarity (n *) of the solvent increased , the absorbance maximum shifted to lower energy levels (red ) due to hydrogen bonding type interactions . Several commercial surfactants were studied : Pluronics ® ( L31 , L92 , 17R2 ) , Zonyl ® FSN , lauryl ether ethoxy lato glycolic acid ( Gele ) . . N * values ​​for five systems studied consist indicator- H20- surfactant - scC02 indicated formation of microenvironments changing with increasing pressure . The values ​​obtained are comparable to the non-aromatic hydrocarbons . Higher values ​​of n * correspond to lndicator -H20 - 17R2 - scC02 pluronic system ( -0.22 to 0.05) at pressures and temperatures ranging from 91-221 bar and 313-323 K respectively. Compared with the other surfactants, Pluronic 17R2 has proven to be the most stable . This stability is due to the structure (PPO -EO- PPO) by allowing interaction trap H20 strong hydrogen bridges . The implemented system has proven to be sensitive to the solute ( drug drug) . Although the values ​​of n * suggest that there is aqueous environment , different behaviors for acetaminophen and imipramine HCI were observed . This suggests different intermolecular interactions between the components that influence the stability and performance of the surfactants .